Recent Advances and Challenges in the Production of Hydroxylated Natural Products Using Microorganisms - Chang Sun; Rumei Zeng; Tianpeng Chen; Yibing Yang; Yi Song; Qiang Li; Jie Cheng; Bingliang Liu (Fermentation)
Hydroxylation reaction is a significant source of structural diversity in natural products (NPs), playing a crucial role in improving the bioactivity, solubility, and stability of natural product molecules. This review summarizes the latest research progress in the field of natural product hydroxylation, focusing on several key hydroxylases involved in the biosynthesis of NPs, including cytochrome P450 monooxygenases, α-ketoglutarate-dependent hydroxylases, and flavin-dependent monooxygenases. These enzymes achieve selective hydroxylation modification of various NPs, such as terpenoids, flavonoids, and steroids, through different catalytic mechanisms. This review systematically summarizes the recent advances on the hydroxylation of NPs, such as amino acids, steroids, terpenoids, lipids, and phenylpropanoids, demonstrating the potential of synthetic biology strategies in constructing artificial biosynthetic pathways and producing hydroxylated natural product derivatives. Through metabolic engineering, enzyme engineering, genetic engineering, and synthetic biology combined with artificial intelligence-assisted technologies, a series of engineered strains have been successfully constructed for the efficient production of hydroxylated NPs and their derivatives, achieving efficient synthesis of hydroxylated NPs. This has provided new avenues for drug development, functional food, and biomaterial production and has also offered new ideas for the industrial production of these compounds. In the future, integrating artificial synthetic pathway design, enzyme directed evolution, dynamic regulation, and artificial intelligence technology is expected to further expand the application of enzyme-catalyzed hydroxylation reactions in the green synthesis of complex NPs, promoting research on natural product hydroxylation to new heights.